2003
DOI: 10.1023/b:jarg.0000006709.61216.6f
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Pinopode and αv 3 Integrin Expression Is Not Impaired in Infertile Patients with Endometriosis

Abstract: Purpose : To investigate endometrial receptivity in terms of pinopode formation and αvβ3 integrin expression in infertile women with endometriosis during natural cycles. Methods : We investigated the expression of αvβ3 integrin and pinopode formation in the endometrium of 12 infertile patients with stage I or II endometriosis as the only cause of infertility, 12 infertile patients having unexplained infertility, and 12 fertile women who were undergoing tubal sterilization. Two endometrial biopsies (postovulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…Regarding αvβ3 integrin, the findings corroborate the data of the only two studies that evaluated its levels in the eutopic endometrium of infertile patients with endometriosis I/II by immunohistochemistry and did not identify differences when compared to infertile and fertile controls (Ordi et al, 2003;Casals et al, 2012). Nevertheless, in both studies, the infertile control group consisted of patients with unexplained infertility, which could represent a sampling bias, since we cannot exclude a possible endometrial factor in these cases.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Regarding αvβ3 integrin, the findings corroborate the data of the only two studies that evaluated its levels in the eutopic endometrium of infertile patients with endometriosis I/II by immunohistochemistry and did not identify differences when compared to infertile and fertile controls (Ordi et al, 2003;Casals et al, 2012). Nevertheless, in both studies, the infertile control group consisted of patients with unexplained infertility, which could represent a sampling bias, since we cannot exclude a possible endometrial factor in these cases.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, in both studies, the infertile control group consisted of patients with unexplained infertility, which could represent a sampling bias, since we cannot exclude a possible endometrial factor in these cases. Added to this, the testing power of the Ordi et al (2003) study was low, while Casals et al (2012) did not report this data, making it impossible to draw consistent conclusions about the role of this integrin in the disease-related infertility. To date, there are no studies evaluating HBEGF expression in infertile women with endometriosis, once it is the first study to rule out differences in this gene among the studied groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is during the 20-24 days of the menstrual cycle that can accept the embryo [27]. Existing research found that many elements were involved in the regulation of endometrial receptivity such as integrin anb3 [28], a1b1 [29], leukemia inhibiting factor (LIF) [30], leptin [31], placental protein14 (PP14) [32], etc. These factors play important roles in the formation process of endometrial receptivity, but still it is unable to fully reveal molecular bp (c) mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These same investigators demonstrated absent integrin expression in 44% of endometriosis patients [7]. This finding, however, has not been consistently demonstrated [8,9].…”
mentioning
confidence: 91%